The suspense of trade agreements - Filip Tarlea (ETH Zurich, KOF Swiss Economic Institute, 2018)
Preferential trade agreements (PTAs) are signed between two or more countries following the conclusion of the negotiation process. The duration of this process varies considerably across existing trade agreements and ranges between 316 and 5125 days. This paper presents the consequences of the length of the negotiation process on trade growth. The contribution of this paper to the literature is three- fold. Firstly, it includes as a determinant of trade a new variable that captures negotiations duration for the largest number of PTAs possible, covering all such events from January 1988 until October 2014. This unveils yet another previously ignored feature of PTAs (as trade driver) that leaves results based on a dichotomous PTA status in question. Secondly, this paper evaluates for the rst time the anticipa- tion effects of a PTA, concentrating solely on the negotiation period. Lastly, methodologically, this paper introduces for the first time in the international economics literature a dose response-function approach permitting continuous treatment and many non-treated units. The paper concludes that - ceteris paribus - lengthy PTA negotiations undermine trade growth
Keywords: F10; F12; F17; 330; Trade agreements; Negotiations; Enforcement; Uncertainty